Augmentation of Primary ACL Reconstruction With a Modified Ellison Lateral Extra-articular Tenodesis in High-Risk Patients: A Pilot Study. Issue 8 (13th August 2021) - Feller, Julian A.; Devitt, Brian M.; Webster, Kate E.; Klemm, Haydn J.
Background: Lateral extra-articular tenodesis (LET) has been used to augment primary anterior cruciate ligament (ACL) reconstruction to reduce the risk of reinjury. Most LET procedures result in a construct that is fixed to both the femur and the tibia. In a modified Ellison procedure, the construct is only fixed distally, reducing the risk of inadvertently overconstraining the lateral compartment. Purpose: To evaluate the use of the modified Ellison procedure in a cohort of patients deemed to be at a high risk of further ACL injury after primary ACL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: Included were 25 consecutive patients with at least 2 of the following risk factors: age <20 years at the time of surgery, previous contralateral ACL reconstruction, positive family history of ACL rupture (parent or sibling), generalized ligamentous laxity (Beighton ≥4), grade 3 pivot shift in the consulting room, a desire to return to a pivoting sport, and an elite or professional status. All patients underwent primary ACL reconstruction with an additional modified Ellison procedure. Postoperatively, patients completed the IKDC subjective knee evaluation form (International Knee Documentation Committee), KOOS Quality of Life subscale (Knee injury and Osteoarthritis Outcome Score), ACL–Return to Sport After Injury Scale, Marx Activity Rating Scale, and SANE score (Single Assessment Numeric Evaluation). Results: At 12-month follow-up, the mean outcome scores were as follows: SANE, 94/100; IKDC, 92/100; Marx, 13/16; ACL–Return to Sport, 85/100; and KOOS, 77/100. At 24 months, return-to-sport data were available for 23 of 25 patients; 17 (74%) were playing at the same level or higher than preinjury and 2 at a lower level. One patient (4%) sustained a contact mechanism graft rupture at 12 months. There were 2 (9%) contralateral ACL injuries, including 1 ACL graft rupture, at 11 and 22 months postoperatively. There was a further contralateral ACL graft rupture at 26 months. Conclusion: The use of the modified Ellison procedure as a LET augmentation of a primary ACL reconstruction to produce a low graft rupture rate appeared to be safe in a cohort considered to be at a high risk of reinjury. The procedure showed promise in terms of reducing further graft injuries.